Hyperactive Boys in Adolescence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The rates of dysfunction among male adolescents with a history of hyperactive behavior in childhood were examined in a follow-up study at the New York State Psychiatric Institute and Long Island Jewish Med Cntr, New York, NY.